1997
DOI: 10.1093/mnras/291.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy clusters in the Perseus-Pisces region -- II. The peculiar velocity field

Abstract: We have measured the mean peculiar motions of 103 early-type galaxies in 7 clusters in the Perseus-Pisces (PP) ridge or PP background, and a further 249 such galaxies in 9 calibrating clusters from the literature, using the inverse Fundamental Plane relation. This relation is found to have a distance error of 20% per galaxy. None of the 6 clusters in the PP ridge has a significant motion with respect to the cosmic microwave background (CMB) frame, but the PP background cluster J8 shows marginal evidence of 'ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…However the exponents of the FP were found to deviate significantly from the virial predictions, a result confirmed by all numerous subsequent studies (e.g. Hudson et al 1997;Scodeggio et al 1998;Pahre, Djorgovski & de Carvalho 1998;Colless et al 2001;Bernardi et al 2003). In particular, a recent determination of the plane, for the ATLAS 3D volume-limited survey (Cappellari et al 2011), with σ e measured from integral-field stellar kinematics within R e , gives L ∝ σ Cappellari et al 2013b).…”
Section: Cappellarisupporting
confidence: 75%
“…However the exponents of the FP were found to deviate significantly from the virial predictions, a result confirmed by all numerous subsequent studies (e.g. Hudson et al 1997;Scodeggio et al 1998;Pahre, Djorgovski & de Carvalho 1998;Colless et al 2001;Bernardi et al 2003). In particular, a recent determination of the plane, for the ATLAS 3D volume-limited survey (Cappellari et al 2011), with σ e measured from integral-field stellar kinematics within R e , gives L ∝ σ Cappellari et al 2013b).…”
Section: Cappellarisupporting
confidence: 75%
“…Han & Mould (1992) confirmed this result independently using a whole sky TF sample of 21 clusters. Hudson et al (1997) combined their inverse FP relation measurements of seven clusters in the PP region with data of nine other clusters from the literature and concluded that the whole region has a mean CMB frame bulk motion of 420 ± 280 km s −1 towards galactic coordinates 1 h = H0/(100 km s −1 Mpc −1 ).…”
Section: Previous Studies Of Perseus-piscesmentioning
confidence: 99%
“…For example, several studies have found that the coefficients of the structural relations remain stable when considering different wavelengths (Bender et al 1992;Bender et al 1998;Bernardi et al 2003b;Bernardi et al 2003c;La Barbera et al 2005;La Barbera et al 2008). However, other studies show that the structural relations depend on wavelength (Jørgensen et al 1996;Hudson et al 1997;Pahre et al 1998;Scodeggio et al 1998;Jun & Im 2008). Several studies have shown that the structural relations and/or the structural parameters of galaxies are affected by the environment (Bender et al 1992;Bender et al 1998;Trujillo et al 2001;Trujillo et al 2002;Bernardi et al 2003b;Aguerri et al 2004;Gutiérrez et al 2004;Denicoló et al 2005;Jørgensen et al 2005), although other studies have found the opposite conclusion (de la Rosa et al 2001;Treu et al 2001;Evstigneeva et al 2002;Gonzáles-García & van Albada 2003;Reda et al 2004;Reda et al 2005;Nigoche-Netro et al 2007).…”
Section: Introductionmentioning
confidence: 99%